2018
DOI: 10.1021/acssuschemeng.8b02649
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Chemical Functionality of Technical Lignin Using Ethylene Carbonate for Hydroxyethylation and Subsequent Greener Esterification

Abstract: Full utilization of plant-based feedstocks for sustainable societies must include the valorization of lignin, an abundant aromatic component of the cell wall of plant stems, in processes that follow green chemistry principles. However, one of the major issues limiting lignin utilization is the chemical nonuniformity of the isolated polymer, along with the thermal sensitivity of the free phenolics which hinders processing at elevated temperatures. To address these issues, free phenolics and carboxylic acids of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 37 publications
0
99
1
Order By: Relevance
“…After purging nitrogen gas to remove air, the reaction proceeded in an oil bath under 120°C for 2.5 h. At the end of the reaction, the solution was poured slowly into 400 ml pH = 2 aqueous sulfuric acid with continuous stirring to precipitate modified lignin. The mixture was then filtered by 0.45 ÎŒm PVTF membrane, followed by washing with another 400 ml distilled water until neutral pH and dried by freeze dryer (Liu et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After purging nitrogen gas to remove air, the reaction proceeded in an oil bath under 120°C for 2.5 h. At the end of the reaction, the solution was poured slowly into 400 ml pH = 2 aqueous sulfuric acid with continuous stirring to precipitate modified lignin. The mixture was then filtered by 0.45 ÎŒm PVTF membrane, followed by washing with another 400 ml distilled water until neutral pH and dried by freeze dryer (Liu et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The direct esterification (catalyst-free esterification) was adopted to obtain esterified lignin following our previous procedure (Liu et al, 2018, 2019). Specifically, 3 g hydroxyethyl lignin was mixed with 30 ml oleic acid in a round bottom flask, which was heated under 180°C (oil bath) for 24 h. After cooling down, the samples were mixed with filter aids (Celite 545, Sigma Aldrich) and washed by 300 ml aqueous ethanol (75% v/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lignin is less useful due to this complicated structure, and only about 2% is used as a dispersant, an adhesive, or a surfactant, and most of the lignin produced as a by-product is discarded or incinerated [6]. Most recently, Yin et al [7] reported that lignin has a number of functional groups including hydroxyl, methoxyl and carbonyl groups, and thus can be utilized as a raw material for chemical manufacture through chemical modification techniques such as oxypropylation and epoxidation [8]. Some researchers have found that materials derived from the chemical modification of lignin can be utilized as raw materials for making plastics such as polyurethanes and polyesters in the manufacture of plastics [9,10], as well as raw materials for phenolic resins, epoxy resins and carbon fiber products.…”
Section: Introductionmentioning
confidence: 99%
“…ASKL is reported to have a higher phenolic content and a highly modified structure that may have led to the increase in yield and vanillin selectivity. 11,42 Further, AIKL that has a relatively greater amount of ÎČ-O-4 linkages showed limited production of vanillin relative to ASKL. Along similar lines, milled wood lignin from pine, subjected to significantly less processing than kraft lignin, was also depolymerized under the same conditions with Fe@MagTEMPO.…”
Section: Oxidative Depolymerization Of Kraft Ligninmentioning
confidence: 99%